Modern Approaches to Skin Care - Guthrie, Ashley; Kadakia, Sameep; Hu, Shirley; Sawhney, Raja; Schumacher, Jennifer; Ducic, Yadranko (Facial Plastic Surgery, 2017)
Recent years have seen an increased interest in minimally invasive and noninvasive cosmetic surgery and facial aesthetics. There has been a concomitant surge in the focus on skin care, which, by nature, is minimally invasive, and an exponential growth in the popularity and availability of minimally invasive dermatologic procedures and products. This review seeks to provide an overview of the most commonly employed skin care modalities, such as their mechanisms, indications for use, advantages and disadvantages, and side effects. The authors aim to provide the audience with a fundamental understanding of the options currently available to cosmetic surgeons and practitioners. Topics include retinoids, chemical peels, skin-lightening agents, lasers, microneedling, topical antioxidants, and injectables.
Keywords: skin care; modern; topical; laser; injectables